PENGARUH TINGKAT PENDIDIKAN, PELATIHAN, DAN PENGALAMAN MENGAJAR TERHADAP KINERJA GURU PADA SMP NEGERI 3 SEGERI KABUPATEN PANGKEP - Muhammad Isbat; Muh Yunus; Husain AS (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2021)
The aims of this study are to: (1) Explain the effect of Education Level on Teacher Performance. (2) Explaining the effect of training on teacher performance. (3) Explaining the effect of Teaching Experience on Teacher Performance. (4) Explaining the influence of Education, Training and Teaching Experience on Teacher Performance at SMP Negeri 3 Segeri, Pangkep Regency. Collecting data using questionnaires, documentation, observation, and interviews. The results of the research that have been carried out state that (1) the level of education has a negative and significant influence on teacher performance at SMP Negeri 3 Segeri, Pangkep Regency. (2) There is a significant positive effect of training on teacher performance at SMP Negeri 3 Segeri, Pangkep Regency. (3) There is a significant positive effect of Pursuit Experience on Teacher Performance at SMP Negeri 3 Segeri, Pangkep Regency. (4) There is a simultaneous positive and significant effect between the level of education, training and teaching experience on teacher performance at SMP Negeri 3 Segeri, Pangkep Regency. Keywords: Education, Training, Teaching Experience and Performance